Bacillus thuringiensis Berliner Allergy Mosquito larvae Different doses of pesticides - Mohammed, Abdullah Ibrahim; Bieyu, Salih Hamd (Al-Mukhtar Journal of Sciences, 1992)
The inhibition of spore germinaton of the Bacillus thuringiensis (a mosquito Carvicide) was studied on a nutrient me dium using 5 chemical insecticides. Dif. lubenzeron was found to be the least inhibitory, while methoprene, cyromazine and abate were moderate of all insecticides tested; pesguard was the most inhibitory. The significance of mixing microbial agents and chemical pesticides for IPM system was also emphasized.